Sperm DNA Fragmentation Index: A Comparison Study of Success Rates among Natural, Intrauterine Insemination (IUI) and In Vitro Fertilization (IVF)-Intra Cytoplasmic Sperm Injection (ICSI) Pregnancy Programs - Silvia Werdhy Lestari; Eva Zakiyah; Gita Pratama (HM Publisher, 2022)
Background: Some studies have reported a relationship between the sperm DNA fragmentation index (DFI) and the rate of fertilization and pregnancy. This study was designed to assess the mean sperm DNA fragmentation in pregnancies that occur in infertile couples, whether in natural pregnancy, intrauterine insemination (IUI), and in vitro fertilization (IVF) – intra cytoplasmic injection (ICSI). Methods: This research is an observational analytic study with a cross-sectional design. The sample taken in this study were infertile patients that underwent natural pregnancy or IUI or IVF-ICSI at Yasmin Infertility Clinic of Dr. Ciptomangunkusumo Hospital period 2018-2020 with a consecutive sampling technique. The research data was processed and analyzed by the Mann-Whitney test using the SPSS application. Results: The mean DFI of sperm in men with infertile couples who successfully conceived naturally was 10.7% (mild), while IUI was 20.4% (moderate), and IVF-ICSI was 30.5% (poor). The mean DFI in semen samples of men from infertile couples who underwent a natural program was significantly lower in those who successfully conceived compared to those who did not. Similar results were also shown in the IUI and IVF-ICSI programs, which showed a significantly lower DFI compared to non-pregnant women. Conclusion: DFI can be applied as a marker for selecting the type of pregnancy program in infertility management.